(untitled) (Scientific journal of the Fergana State University, 2023)
The modern direction of linguistics in quality, the main attention of linguoculturology is paid to the study of cultural codes. Cultural codes-act as the key in increasing the national-cultural image of a particular people. The following will analyze the study of the somatic code and the meaning it represents, as well as their main characteristics.